Students’ Perception of the Use of Cartoon Movie as a Media in Learning Vocabulary at Senior High School - Suciati; Sukmawati; Cayati; Sujarwo (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2024)
The purpose of this study is to analyse students’ perceptions of the use of cartoon films as a medium in vocabulary learning. The subjects in this study were 36 students in the tenth grade of SMA Negeri 10 Gowa for the 2023/2024 school year using purposive sampling techniques. This study used a qualitative descriptive method. The data collection techniques in this study were interviews and field records. The data analysis techniques used in this study were reducing data, displaying data, and drawing conclusions. Based on the study results, it was shown that the respondents used three aspects of perception, namely the cognitive aspect, the affective aspect and the conative aspect. Of the three aspects, there were two dominant aspects, namely the cognitive and the affective aspects. The results of students’ perceptions show that the use of cartoon movies as a medium in vocabulary learning is very good because students get a lot of new vocabulary, students became aware of word pronunciation and correct word writing, become more happy to learn English, more enthusiastic to learn and remember a lot of new vocabulary.